Inter-firm dependency and the adoption of e-procurement system: Case study of Malaysian manufacturers - Nik Abdullah, Nik Ab. Halim (2014)
E-procurement is an automated purchasing system that may help improve the coordination and efficiency of procurement activities between component or materials suppliers and manufacturer. There has been much research conducted to identify factors that encourage the adoption and diffusion of e-procurement technology but there is no evidence of study that looks from the resource dependency theory perspective.Therefore, the objective of this study is to investigate the impact of dependency among supply chain members on the diffusion of an e-procurement adoption system by using a case-study interview method.This paper will discuss the findings of case study interviews conducted with two manufacturers in Malaysia that supply components and parts to a relatively larger manufacturer in Malaysia.With support from the resource dependency theory, the findings of this paper highlight the extent to which supplier's dependency to their major business partners may lead to the adoption of e-procurement system.